Strega Nona an old tale - DePaola, Tomie 1934- (New York Scholastic Inc., 1975)
When Strega Nona leaves him alone with her magic pasta pot, Big Anthony is determined to show the townspeople how it works.
Keywords: Folklore -- Italy